Quality of life in patients with systemic lupus erythematosus - Елена Александровна Асеева; V N Amirdzhanova; Т А Лисицына; M V Zavalskaya (Научно-практическая ревматология)
The recent rise in survival rates and therefore in the degree of organ damages due to both disease itself and performed therapy increasingly gives a reason to think about health-related quality of life (QL) in patients with systemic lupus erythematosus (SLE). Numerous studies initiated in the 1980s to asses QL in patients with SLE have revealed considerable impairments in physical, emotional functioning in this category of patients. SLE leads to social dysadaptation, chronic stress, anxiety, and depression. Timely detection of worse QL in patients and correction of depressive disorders improve patient compliance. Six SLE questionnaires were validated to study health-related QL; these were Medical Outcomes Study 36-Item Short Form Health Survey (MOS SF-36) SLE Symptom checklist, SLE QL Questionnaire (SLEQol), Lupus QL Questionnaire (LupusQol), LQol, and Lupus Patient Reported Outcome Tool (LupusPRO). The general MOS SF-36 and specific Lupus Qol that has been developed for SLE patients are available in Russian. To study QL in the patients at the present stage of rheumatology development is an important component of SLE cura-tion both in real clinical practice and during international clinical trials as one of the components of therapy assessment.